Sino-India difference in collectivism and its association with cultural heritage concerning argumentation - Xiaopeng Ren; Xiaopeng Ren; Dongqin Kuai; Dongqin Kuai (Frontiers in Psychology, 2023)
Cross-cultural studies from a global perspective contend that China and India are both collectivistic cultures. However, it remains unclear whether and why China and India differ in their collectivism. This study examines whether the cultural heritage concerning argumentation explains why Chinese people are more collectivistic than Indians. Convenient samples were taken from online surveys (NChina = 398, NIndia = 418), and 186 participants from the United States were included in the contrast group. In multiple methods conducted here, the Chinese respondents scored higher in holistic thought, compatriotism, nepotism, familism, and self-interdependence than the Indian respondents, while scoring lower in assertiveness and argumentativeness. Although China and India were more collectivistic than the United States, these findings support the hypothesis that Chinese people are more collectivistic than Indians. The study extended our knowledge of individualism–collectivism beyond east–west comparison.